Transatlantic space politics : competition and cooperation above the clouds - Wang, Sheng-Chih, 1979- (Abingdon [England] ; New York : Routledge, 2013)
"This book examines transatlantic politics through an analysis of 60 years of US-European strategic interaction in space. The significance of space politics for the study of transatlantic relations receives surprisingly little scholarly attention. As a theatre of interaction, transatlantic space politics reflects the vicissitudes of European and US power in the international system. An understanding of space politics is therefore vital in understanding the status and prospect of the transatlantic order. Using established IR theories, the author investigates transatlantic space politics and proposes a theoretical explanation, which is distinct from the conventional wisdom of the transatlantic security community. More specifically, he distinguishes between the constitutive and regulatory effects of the transatlantic security community, an approach rarely employed in other research in the field. Overall, this book suggests not only that the transatlantic institutional pillar requires repair, but also that the ideational factors need to be revitalised in order to consolidate the transatlantic alliance.This book will be of much interest to students of space power, transatlantic politics, strategic studies, foreign policy and IR/security studies in general"--
Introduction : the multi-faceted transatlantic space politics -- History matters : space policy evolution in the United States and Europe -- Cutting the umbilical cord : transatlantic competition in the field of space transportation -- Springboard toward lunar and solar space : transatlantic cooperation in the International Space Station Program -- Europe opens its eyes : transatlantic dispute in the field of satellite navigation -- Dual space dominance versus autonomy in space : developing cases of transatlantic space politics -- Conclusions : thinking beyond the canopy.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: United States. -- National Aeronautics and Space Administration; European Space Agency; Astronautics and state -- United States; Astronautics and state -- European Union countries; Astronautics -- International cooperation; National security -- United States; National security -- European Union countries; United States -- Foreign relations -- European Union countries; European Union countries -- Foreign relations -- United States; Electronic books